The longitudinal relationship between fatigue, depression, anxiety, disability, and adherence with cognitive status in patients with early multiple sclerosis treated with interferon beta-1a - Hanne van Ballegooijen; Karin van der Hiele; Christian Enzinger; Gert de Voer; Leo H. Visser (eNeurologicalSci, 2022)
Background: Cognitive dysfunction is common in multiple sclerosis and may worsen with reduced treatment adherence. We examined longitudinal relationships between anxiety, depression, fatigue, disability and adherence with cognitive status in patients with relapsing-remitting multiple sclerosis (MS) treated with interferon beta-1a in four countries. Methods: The Confidence study is a prospective study in 165 people with MS with four visits (baseline/12/24/36 months). Physical and psychological symptoms were assessed using standardized questionnaires. Adherence was calculated as the number of injections divided by number of expected injections. Cognitive status was assessed by the Brief Repeatable Battery of Neuropsychological Tests and converted to a global Z-score. Results: At baseline, mean age was 35.7 ± 11 years and 66% were female (n = 109). Adherence to treatment was very high throughout the study (>99%). A depression score ≥ 8 was significantly associated with a higher risk of low cognitive status compared with a lower score (0–7): relative risk 1.79 (1.14–2.83) adjusted for education and time since diagnosis. The P-value-for-time was not significant (P = 0.304) meaning that associations existed since baseline and remained stable during follow-up. Conclusion: Our findings provide evidence for a longitudinal association between depression and low cognitive status in patients treated with interferon beta-1a in routine medical practice.